Preparation method of foamy copper-based catalytic material for electrochemical degradation of chloramphenicol sewage

By loading poly3-thiophene amide on the surface of the foamed copper matrix and combining it with polyaminostyrene copper-coordinated polymer, an efficient foamed copper-based catalytic material was prepared, which solved the problem of insufficient performance of chloramphenicol wastewater treatment catalytic material in the prior art, and achieved efficient and stable large-scale industrial treatment effect.

CN119857534AActive Publication Date: 2025-04-22NORTH CHINA UNIVERSITY OF TECHNOLOGY
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202510065127.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-16
Publication Date
2025-04-22
Estimated Expiration
2045-01-16

AI Technical Summary

Technical Problem

In the prior art, the catalytic material that electrochemical reduction and degrades chloramphenicol wastewater has poor reduction and degradation performance, and the repeated and stable use performance is not ideal, which cannot meet the requirements of large-scale industrial treatment.

Method used

By supporting poly3-thiophene amide on the surface of the foamed copper matrix and combining with polyaminostyrene copper-coordinated polymer, a foamed copper-based catalytic material with high efficiency reduction and degradation properties and excellent cycle and reuse stability was prepared.

Benefits of technology

It achieves efficient chloramphenicol degradation performance and has excellent cycle and reuse stability, which is suitable for the demand for large-scale industrial electrochemical reduction and degradation of chloramphenicol wastewater.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119857534A_ABST
    Figure CN119857534A_ABST
Patent Text Reader

Abstract

The invention provides a preparation method of a foamy copper-based catalytic material for electrochemical degradation of chloramphenicol sewage. The preparation method comprises the following steps: (1) loading poly-3-thiophene amide on the surface of a foamy copper matrix; (2) synthesizing polyamino styrene; and (3) converting the poly (3-thiophene amide) on the surface of the foamy copper substrate into the poly (3-thiophene amide) / poly (amino styrene) copper coordination polymer. The foamy copper-based catalytic material prepared by the method disclosed by the invention has efficient and excellent reductive degradation performance and excellent recycling stability, and can meet the requirements of large-scale industrial electrochemical reductive degradation of chloramphenicol sewage.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of chloramphenicol-containing wastewater treatment, in particular to a method for preparing a foam copper-based catalytic material for electrochemically degrading chloramphenicol wastewater. Background Art

[0002] Chloramphenicol is an amide antibiotic and a broad-spectrum antibacterial drug. Chloramphenicol combines with the 50S subunit of bacterial ribosomes to reduce the activity of peptidyl transferase and prevent the synthesis of bacteria, thereby achieving antibacterial effects. Chloramphenicol has inhibitory effects on Gram-negative bacteria, Gram-positive bacteria, Streptococcus pneumoniae, Haemophilus influenzae, meningococci, etc. Chloramphenicol has a strong killing effect on Gram-negative bacteria and other bacteria under high concentration conditions. Since chloramphenicol is widely used in human health care, bacterial prevention and control and disease treatment in animal husbandry, the amount of chloramphenicol entering the soil and water environment is increasing. The toxic and side effects of chloramphenicol include: bone marrow suppression, aplastic anemia, neurotoxicity, allergies and gastrointestinal damage. Chloramphenicol is difficult to degrade naturally, and the threat posed by chloramphenicol wastewater is extremely serious.

[0003] The electrochemical reduction degradation technology of halogenated organic matter is to form active H* through electrochemical cathode catalytic materials, and the active H* directly reacts with the halogen atoms of halogenated organic matter to separate from the halogenated organic matter, thereby achieving the purpose of degrading the halogenated organic matter. If the electrochemical cathode catalytic material has excellent reduction degradation performance, the electrochemical reduction degradation technology will be an effective way to treat halogenated organic wastewater.

[0004] However, in the field of chloramphenicol wastewater treatment, the reduction and degradation performance of its electrochemical reduction and degradation catalytic materials is still poor, the repeated stable use performance is not ideal, and it cannot meet the requirements of large-scale industrial electrochemical reduction and degradation treatment of chloramphenicol wastewater. Summary of the invention

[0005] In order to overcome the shortcomings of the prior art, the present invention provides a method for preparing a foam copper-based catalytic material for electrochemical degradation of chloramphenicol wastewater. The foam copper-based catalytic material prepared by the method has high efficiency and excellent reduction degradation performance, and has excellent cyclic repeated use stability, and can be suitable for the requirements of large-scale industrial electrochemical reduction degradation of chloramphenicol wastewater.

[0006] The technical solution adopted by the present invention to solve its technical problem is:

[0007] The present invention provides a method for preparing a foam copper-based catalytic material for electrochemically degrading chloramphenicol wastewater, comprising the following steps:

[0008] Step [1]: loading poly (3-thiopheneamide) on the surface of the copper foam substrate;

[0009] Step [2] synthesizing polyaminostyrene;

[0010] Step [3] converts the poly (3-thiopheneamide) on the surface of the foam copper substrate into a poly (3-thiopheneamide) / polyaminostyrene copper coordination polymer.

[0011] Preferably, the step [1] specifically includes the following operations:

[0012] a1. Add 3-trithiophenecarboxylic acid hydrazine and 3-thiopheneacetyl chloride to ethylene glycol dimethyl ether and mix to form a base liquid A; add sodium bisulfite and urea to deionized water and mix to form a catalytic regulator;

[0013] a2. Add a certain amount of catalytic regulating liquid to the base liquid A to form a loading liquid, immerse the foam copper sample in the loading liquid, and react at room temperature for 20-24 hours to obtain a foam copper with poly (3-thiopheneamide) loaded on the surface, which is recorded as intermediate A.

[0014] Preferably, in step a1, the amount of 3-terthiophenecarboxylic acid hydrazine added to each liter of the base liquid A is 80-110 g, and the amount of 3-thiopheneacetyl chloride added is 40-80 g; the concentration of sodium bisulfite in the catalytic regulating liquid is 10-20 g / L, and the concentration of urea is 30-60 g / L.

[0015] Preferably, in step a2, the volume ratio of the catalytic regulating liquid to the base liquid A in the loading liquid is 1-2:5-9; and the weight of the foam copper immersed in each liter of the loading liquid is 130-170 g.

[0016] Preferably, the step [2] specifically includes the following operations:

[0017] b1. Adding 2-aminostyrene and N,N-dimethylaniline to dimethyl sulfoxide, mixing to form an organic synthesis liquid; adding urotropine to deionized water, mixing to form an inorganic catalyst liquid;

[0018] b2. Add a certain amount of inorganic catalyst liquid to the organic synthesis liquid, react at room temperature for 22-26 hours, filter the solid phase product, and dry it under ventilation at room temperature for 10-12 hours to obtain polyaminostyrene.

[0019] Preferably, in step b1, the amount of 2-aminostyrene added to each liter of the organic synthesis liquid is 110-140 mL, and the amount of N,N-dimethylaniline added is 30-70 mL; the concentration of hexamethylenetetramine in the inorganic catalyst liquid is 40-60 g / L.

[0020] Preferably, in step b2, the volume ratio between the inorganic catalyst liquid and the organic synthesis liquid is 5-7:2-4.

[0021] Preferably, the step [3] specifically includes the following operations:

[0022] c1. Add copper methyl isobutylene, copper methanesulfonate and β-naphthalenesulfonic acid to deionized water and mix to form a base solution B; add 3-terthiophenecarboxylic acid hydrazine to ethylene glycol dimethyl ether and mix to form an additive solution; add a certain amount of the additive solution to the base solution B and mix to form a conversion solution;

[0023] c2. Immerse the intermediate A in the conversion solution, add a certain amount of polyaminostyrene to the conversion solution, heat to 70-90°C, react for 8-12 hours, take out the foam copper sample, and dry it under ventilation at room temperature for 5-8 hours to obtain a foam copper with a surface loaded with poly (3-thiopheneamide) / polyaminostyrene copper coordination polymer, i.e., the foam copper-based catalytic material.

[0024] Preferably, in step c1, the amount of methyl isobutylene copper added to each liter of the base liquid B is 2 to 8 g, the amount of copper methane sulfonate added is 130 to 190 mL, and the amount of β-naphthalenesulfonic acid added is 20 to 50 g; the amount of 3-terthiophenecarboxylic acid hydrazine added to each liter of the additive liquid is 25 to 45 g; the volume ratio between the additive liquid and the base liquid B in the conversion liquid is 2 to 3:7 to 9.

[0025] Preferably, in step c2, the weight of the intermediate A immersed in each liter of the conversion liquid is 100-130 g, and the amount of polyaminostyrene added to each liter of the conversion liquid is 80-140 g.

[0026] The positive effects of the present invention: the copper-foam-based catalytic material prepared by the method of the present invention, the poly-3-thiopheneamide / polyaminostyrene copper coordination polymer loaded on the copper-foam surface, is formed by each copper ion accepting four pairs of lone pairs of electrons provided by two oxygen atoms of two carbonyl groups of poly-3-thiopheneamide and two amino nitrogen atoms of polyaminostyrene to form coordination bonds. Based on the above structural characteristics: the sulfur atom of poly-3-thiopheneamide and the thiophene ring have conjugated bonds to form an energy band structure with good conductive properties; the conductive properties of polyaminostyrene in the electrochemical reduction degradation process are relatively weak, therefore, the coordination polymer can not only ensure a faster reaction rate in the electrochemical reduction degradation of chloramphenicol, but also ensure the relative stability of the composite coordination polymer of poly-3-thiopheneamide and polyaminostyrene; at the same time, the copper ions of the coordination polymer have unsaturated d orbitals, which can promote the formation of surface active hydrogen H*, thereby promoting the active hydrogen H* to dechlorinate and reduce the degradation of chloramphenicol; in addition, the prepared copper-foam-based catalytic material also has a relatively high hydrogen evolution overpotential, which can effectively inhibit the occurrence of hydrogen evolution side reactions in the electrochemical reduction degradation of chloramphenicol.

[0027] In summary, the foamed copper-based catalytic material prepared according to the present invention has high-efficiency and excellent reduction degradation performance, and has excellent cyclic reuse stability, and can be suitable for the requirements of large-scale industrial electrochemical reduction degradation of chloramphenicol wastewater. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1 It is a schematic diagram of the preparation process of the foam copper-based catalytic material of the present invention;

[0029] Figure 2 is a schematic diagram of the microstructure of the foam copper-based catalytic material of the present invention;

[0030] Figure 3 The relative concentrations of residual chloramphenicol in the simulated chloramphenicol-containing wastewater treated with concentrations of 20 mg / L and 10 mg / L, respectively, in Example 1, Comparative Example 1 and Comparative Example 2 of the present invention;

[0031] Figure 4 It is a relationship diagram between the number of times of use and the relative concentration of residual chloramphenicol when Example 1, Comparative Example 1 and Comparative Example 2 are repeatedly used to treat simulated chloramphenicol-containing sewage with a concentration of 20 mg / L;

[0032] Figure 5 It is a relationship diagram between the number of uses and the relative concentration of residual chloramphenicol when Example 1, Comparative Example 1 and Comparative Example 2 are repeatedly used to treat simulated chloramphenicol-containing wastewater with a concentration of 10 mg / L. DETAILED DESCRIPTION

[0033] Reference Figure 1 The present invention provides a method for preparing a foam copper-based catalytic material for electrochemically degrading chloramphenicol wastewater, comprising the following steps:

[0034] Step [1] loading poly (3-thiopheneamide) on the surface of the copper foam substrate comprises the following operations:

[0035] a1. Add 3-terthiophenecarboxylic acid hydrazine and 3-thiopheneacetyl chloride to ethylene glycol dimethyl ether and mix to form a base liquid A, wherein the amount of 3-terthiophenecarboxylic acid hydrazine added to the base liquid A is 80 to 110 g, and the amount of 3-thiopheneacetyl chloride added is 40 to 80 g; sodium bisulfite and urea are added to deionized water to form a sodium bisulfite concentration of 10 to 20 g / L, urea concentration of 30 to 60 g / L catalytic regulator;

[0036] a2. A certain amount of catalytic regulating liquid is added to the base liquid A to form a loading liquid (the volume ratio of the catalytic regulating liquid to the base liquid A in the loading liquid is 1-2:5-9), and the foamed copper sample is immersed in the loading liquid (the weight of the foamed copper immersed in each liter of the loading liquid is 130-170 g), and the reaction is carried out at room temperature for 20-24 hours to obtain a foamed copper with poly 3-thiopheneamide loaded on the surface, which is recorded as intermediate A.

[0037] In this step, 3-terthiophenecarboxylic acid hydrazine and 3-thiopheneacetyl chloride are polymerized on the surface of the foam copper substrate to form poly 3-thiopheneamide, and the structural formula of the poly 3-thiopheneamide is:

[0038]

[0039] Step [2] synthesizing polyaminostyrene, specifically comprising the following operations:

[0040] b1. Adding 2-aminostyrene and N,N-dimethylaniline to dimethyl sulfoxide, mixing to form an organic synthesis liquid, wherein the amount of 2-aminostyrene added per liter of the organic synthesis liquid is 110 to 140 mL, and the amount of N,N-dimethylaniline added is 30 to 70 mL; adding urotropine to deionized water, mixing to form an inorganic catalyst solution having a urotropine concentration of 40 to 60 g / L;

[0041] b2. The volume ratio of the inorganic catalyst liquid to the organic synthesis liquid is 5 to 7:2 to 4, and the inorganic catalyst liquid is added to the organic synthesis liquid, and the reaction is carried out at room temperature for 22-26 hours, and the solid phase product is filtered and dried at room temperature for 10-12 hours to obtain polyaminostyrene.

[0042] In this step, polyaminostyrene is formed by polymerization of 2-aminostyrene, and the structural formula of the polyaminostyrene is:

[0043]

[0044] Step [3] converting the poly (3-thiopheneamide) on the surface of the copper foam substrate into a poly (3-thiopheneamide) / polyaminostyrene copper coordination polymer, specifically comprising the following operations:

[0045] c1. Methyl isobutylene copper, copper methanesulfonate and β-naphthalenesulfonic acid are added to deionized water and mixed to form a base solution B, wherein the amount of methyl isobutylene copper added to the base solution B is 2 to 8 g, the amount of copper methanesulfonate added is 130 to 190 mL, and the amount of β-naphthalenesulfonic acid added is 20 to 50 g; 3-trithiophenecarboxylic acid hydrazine is added to ethylene glycol dimethyl ether to form an additive solution, wherein the amount of 3-trithiophenecarboxylic acid hydrazine added to the additive solution is 25 to 45 g per liter; the additive solution is added to the base solution B in a volume ratio of 2 to 3:7 to 9, and the conversion solution is mixed;

[0046] c2. The intermediate A is immersed in the conversion solution (the weight of the intermediate A immersed in each liter of the conversion solution is 100-130g), and a certain amount of polyaminostyrene is added to the conversion solution (the amount of polyaminostyrene added in each liter of the conversion solution is 80-140g), heated to 70-90°C, reacted for 8-12 hours, and the foam copper sample is taken out and dried under ventilation at room temperature for 5-8 hours to obtain a foam copper with a surface loaded with poly-3-thiopheneamide / polyaminostyrene copper coordination polymer, i.e., the foam copper-based catalytic material, the microstructure of which is shown in the schematic diagram as follows: Figure 2 shown.

[0047] In this step, poly (3-thiopheneamide) and poly (aminostyrene) are used as ligands to form poly (3-thiopheneamide) / poly (aminostyrene) copper coordination polymer with copper ions, and the reaction formula involved is:

[0048]

[0049] The preferred embodiments of the present invention are described below by way of example.

[0050] Example 1

[0051] Preferred embodiment 1 of the present invention provides a method for preparing a foam copper-based catalytic material for electrochemical degradation of chloramphenicol wastewater, comprising the following steps:

[0052] Step [1] loading poly (3-thiopheneamide) on the surface of the copper foam substrate comprises the following operations:

[0053] a1. Add 3-terthiophenecarboxylic acid hydrazine and 3-thiopheneacetyl chloride to ethylene glycol dimethyl ether and mix to form a base liquid A, wherein the amount of 3-terthiophenecarboxylic acid hydrazine added to the base liquid A is 90 g, and the amount of 3-thiopheneacetyl chloride added is 70 g; sodium bisulfite and urea are added to deionized water to form a sodium bisulfite concentration of 16 g / L, urea concentration of 50 g / L catalytic regulator;

[0054] a2. A certain amount of catalytic regulating liquid is added to the base liquid A to form a loading liquid (the volume ratio of the catalytic regulating liquid to the base liquid A in the loading liquid is 1:7), and the foam copper sample is immersed in the loading liquid (the weight of the foam copper immersed in each liter of the loading liquid is 160 g), and the reaction is carried out at room temperature for 23 hours to obtain a foam copper with poly (3-thiopheneamide) loaded on the surface, which is recorded as intermediate A.

[0055] Step [2] synthesizing polyaminostyrene, specifically comprising the following operations:

[0056] b1. Adding 2-aminostyrene and N,N-dimethylaniline to dimethyl sulfoxide, mixing to form an organic synthesis liquid, wherein per liter of the organic synthesis liquid 2-aminostyrene is added in an amount of 130mL, N,N-dimethylaniline is added in an amount of 60mL; adding urotropine to deionized water, mixing to form an inorganic catalyst liquid having a urotropine concentration of 50g / L;

[0057] b2. The volume ratio of the inorganic catalyst liquid to the organic synthesis liquid was 7:2, and the inorganic catalyst liquid was added to the organic synthesis liquid, and the reaction was carried out at room temperature for 25 hours. The solid phase product was filtered and dried at room temperature for 12 hours to obtain polyaminostyrene.

[0058] Step [3] converting the poly (3-thiopheneamide) on the surface of the copper foam substrate into a poly (3-thiopheneamide) / polyaminostyrene copper coordination polymer, specifically comprising the following operations:

[0059] c1. Methyl isobutylene copper, copper methanesulfonate and β-naphthalenesulfonic acid are added to deionized water and mixed to form a base solution B, wherein the amount of methyl isobutylene copper added to the base solution B is 5 g, the amount of copper methanesulfonate added is 160 mL, and the amount of β-naphthalenesulfonic acid added is 40 g; 3-trithiophenecarboxylic acid hydrazine is added to ethylene glycol dimethyl ether to form an additive solution, wherein the amount of 3-trithiophenecarboxylic acid hydrazine added to the additive solution is 40 g per liter; the additive solution is added to the base solution B in a volume ratio of 3:8 to form a conversion solution;

[0060] c2. The intermediate A is immersed in the conversion solution (the weight of the intermediate A immersed in each liter of the conversion solution is 120g), and a certain amount of polyaminostyrene is added to the conversion solution (the amount of polyaminostyrene added in each liter of the conversion solution is 130g), heated to 80°C, reacted for 10 hours, and the foamed copper sample is taken out and dried under ventilation at room temperature for 6 hours to obtain a foamed copper with a surface loaded with a poly (3-thiopheneamide) / polyaminostyrene copper coordination polymer, i.e., the foamed copper-based catalytic material, recorded as Example 1.

[0061] Comparative Example 1

[0062] This comparative example 1 provides a method for preparing a foam copper-based catalytic material for electrochemical degradation of chloramphenicol wastewater, comprising the following steps:

[0063] Step [1] loading poly (3-thiopheneamide) on the surface of the copper foam substrate comprises the following operations:

[0064] a1. Add 3-terthiophenecarboxylic acid hydrazine and 3-thiopheneacetyl chloride to ethylene glycol dimethyl ether and mix to form a base liquid A, wherein the amount of 3-terthiophenecarboxylic acid hydrazine added to the base liquid A is 90 g, and the amount of 3-thiopheneacetyl chloride added is 50 g; sodium bisulfite and urea are added to deionized water to form a sodium bisulfite concentration of 15 g / L, urea concentration of 40 g / L catalytic regulator;

[0065] a2. A certain amount of catalytic regulating liquid was added to the base liquid A to form a loading liquid (the volume ratio of the catalytic regulating liquid to the base liquid A in the loading liquid was 1:6), and the foamed copper sample was immersed in the loading liquid (the weight of the foamed copper immersed in each liter of the loading liquid was 140 g), and the reaction was carried out at room temperature for 20-24 hours to obtain a foamed copper with poly 3-thiopheneamide loaded on the surface, which was recorded as Comparative Example 1.

[0066] Comparative Example 2

[0067] This comparative example 2 provides a method for preparing a foam copper-based catalytic material for electrochemical degradation of chloramphenicol wastewater, comprising the following steps:

[0068] Step [1] loading poly (3-thiopheneamide) on the surface of the copper foam substrate specifically comprises the following operations:

[0069] a1. Add 3-terthiophenecarboxylic acid hydrazine and 3-thiopheneacetyl chloride to ethylene glycol dimethyl ether and mix to form a base liquid A, wherein the amount of 3-terthiophenecarboxylic acid hydrazine added to the base liquid A is 100 g, and the amount of 3-thiopheneacetyl chloride added is 70 g; sodium bisulfite and urea are added to deionized water to form a sodium bisulfite concentration of 15 g / L, urea concentration of 50 g / L catalytic regulator;

[0070] a2. A certain amount of catalytic regulating liquid is added to the base liquid A to form a loading liquid (the volume ratio of the catalytic regulating liquid to the base liquid A in the loading liquid is 2:7), and the foam copper sample is immersed in the loading liquid (the weight of the foam copper immersed in each liter of the loading liquid is 150 g), and the reaction is carried out at room temperature for 23 hours to obtain a foam copper with poly (3-thiopheneamide) loaded on the surface, which is recorded as intermediate A.

[0071] Step [2] synthesizing polyaminostyrene, specifically comprising the following operations:

[0072] b1. Adding 2-aminostyrene and N,N-dimethylaniline to dimethyl sulfoxide, mixing to form an organic synthesis liquid, wherein per liter of the organic synthesis liquid 2-aminostyrene is added in an amount of 130 mL, N,N-dimethylaniline is added in an amount of 40 mL; adding urotropine to deionized water, mixing to form an inorganic catalyst liquid having a urotropine concentration of 50 g / L;

[0073] b2. The volume ratio of the inorganic catalyst liquid to the organic synthesis liquid was 5:3, and the inorganic catalyst liquid was added to the organic synthesis liquid, and the reaction was carried out at room temperature for 24 hours. The solid phase product was filtered and dried at room temperature for 11 hours to obtain polyaminostyrene.

[0074] Step [3] converting the poly (3-thiopheneamide) on the surface of the copper foam substrate into poly (3-thiopheneamide) / polyaminostyrene, specifically comprising the following operations:

[0075] c1. Add β-naphthalenesulfonic acid to deionized water and mix to form a base solution B, wherein the amount of β-naphthalenesulfonic acid added to each liter of the base solution B is 30 g; add 3-trithiophenecarboxylic acid hydrazine to ethylene glycol dimethyl ether and mix to form an additive solution, wherein the amount of 3-trithiophenecarboxylic acid hydrazine added to each liter of the additive solution is 30 g; add the additive solution to the base solution B at a volume ratio of 3:8, and mix to form a conversion solution;

[0076] c2. The intermediate A is immersed in the conversion solution (the weight of the intermediate A immersed in each liter of the conversion solution is 110g), and a certain amount of polyaminostyrene is added to the conversion solution (the amount of polyaminostyrene added in each liter of the conversion solution is 120g), heated to 75°C, reacted for 10 hours, and the foam copper sample is taken out and dried at room temperature for 6 hours to obtain a foam copper loaded with poly 3-thiopheneamide / polyaminostyrene on the surface, which is recorded as Comparative Example 2; wherein the carbonyl group of poly 3-thiopheneamide in this step is The electron-withdrawing group, whose oxygen atom has a greater electronegativity than the carbon atom, has a strong electron-withdrawing ability, and makes the electron pair biased toward the oxygen atom of the carbonyl group; the amine group of polyaminostyrene is an electron-donating group, and the electronegativity of the amine nitrogen is less than that of carbon, and its electrons move toward the benzene ring of polyaminostyrene, which leads to a lower electron density of the amine group, making the nitrogen of the amine group partially positively charged; therefore, the partially positively charged nitrogen of the amine group of polyaminostyrene forms a chemical bond with the oxygen atom of the carbonyl group of poly-3-thiopheneamide, thereby reacting to form poly-3-thiopheneamide / polyaminostyrene. The reaction formula involved in this step is:

[0077]

[0078] In order to analyze the performance of electrochemical reduction degradation of chloramphenicol sewage in Example 1, Comparative Example 1 and Comparative Example 2, chloramphenicol was added to deionized water to form simulated chloramphenicol-containing sewage with chloramphenicol addition amounts of 20 mg / L and 10 mg / L, respectively. 100 ml of simulated chloramphenicol-containing sewage was poured into beakers, and Example 1, Comparative Example 1 and Comparative Example 2 with length, width and thickness dimensions of 4 cm×2 cm×1 cm were placed in beakers, and at the same time, in order to make the electrochemical reduction degradation process of simulated chloramphenicol sewage have sufficient conductivity, sodium sulfate was added to the simulated chloramphenicol sewage, so that the sodium sulfate concentration in the simulated chloramphenicol sewage was 5 g / L. Comparative Example 1, Comparative Example 2 and Example 1 with the above-mentioned sizes were used as cathodes, stainless steel was used as anodes, and the temperature was 4 mA / cm 2 The simulated chloramphenicol wastewater was degraded by constant current electrochemical reduction for 30 minutes, and the residual chloramphenicol concentration in the simulated chloramphenicol wastewater was measured by high performance liquid chromatography. The results are as follows Figure 3 As shown in the figure, it can be seen that the relative concentrations of residual chloramphenicol in the simulated chloramphenicol wastewater of 20 mg / L and 10 mg / L after electrochemical reduction degradation in Example 1 are only 0.02 and 0.01, respectively, which are significantly lower than the relative concentrations of residual chloramphenicol of 0.65 and 0.62 corresponding to Comparative Example 1, and also lower than the relative concentrations of residual chloramphenicol of 0.44 and 0.37 corresponding to Comparative Example 2.

[0079] Under the above-mentioned treatment conditions and treatment time, the relationship between the number of times of use and the relative concentration of residual chloramphenicol was shown as follows: Figure 4 and Figure 5 As shown in the figure, it can be seen that the residual chloramphenicol relative concentration of 100 ml of 20 mg / L and 10 mg / L simulated chloramphenicol sewage in Example 1 is only 0.08 and 0.06 after electrochemical reduction degradation for 15 times (one hour each time), which is significantly lower than the corresponding residual chloramphenicol relative concentration of 0.86 and 0.85 when the comparative example 1 is recycled for 15 times, and also lower than the corresponding residual chloramphenicol relative concentration of 0.64 and 0.56 when the comparative example 2 is recycled for 15 times. Obviously, Example 1 has stable and efficient recyclable characteristics.

[0080] In summary, the foamed copper-based catalytic material prepared according to the present invention has high-efficiency and excellent reduction degradation performance, and has excellent cyclic reuse stability, and can be suitable for the requirements of large-scale industrial electrochemical reduction degradation of chloramphenicol wastewater.

[0081] To illustrate in further detail, three additional examples are provided below.

[0082] Example 2

[0083] Preferred embodiment 2 of the present invention provides a method for preparing a foam copper-based catalytic material for electrochemical degradation of chloramphenicol wastewater, comprising the following steps:

[0084] Step [1] loading poly (3-thiopheneamide) on the surface of the copper foam substrate specifically comprises the following operations:

[0085] a1. Add 3-terthiophenecarboxylic acid hydrazine and 3-thiopheneacetyl chloride to ethylene glycol dimethyl ether and mix to form a base liquid A, wherein the amount of 3-terthiophenecarboxylic acid hydrazine added to the base liquid A is 80 g, and the amount of 3-thiopheneacetyl chloride added is 40 g; sodium bisulfite and urea are added to deionized water to form a sodium bisulfite concentration of 20 g / L, urea concentration of 30 g / L catalytic regulator;

[0086] a2. A certain amount of catalytic regulating liquid is added to the base liquid A to form a loading liquid (the volume ratio of the catalytic regulating liquid to the base liquid A in the loading liquid is 1:5), and the foam copper sample is immersed in the loading liquid (the weight of the foam copper immersed in each liter of the loading liquid is 130 g), and the reaction is carried out at room temperature for 20 hours to obtain a foam copper with poly (3-thiopheneamide) loaded on the surface, which is recorded as intermediate A.

[0087] Step [2] synthesizing polyaminostyrene, specifically comprising the following operations:

[0088] b1. Adding 2-aminostyrene and N,N-dimethylaniline to dimethyl sulfoxide, mixing to form an organic synthesis liquid, wherein per liter of the organic synthesis liquid 2-aminostyrene is added in an amount of 110mL, N,N-dimethylaniline is added in an amount of 30mL; adding urotropine to deionized water, mixing to form an inorganic catalyst liquid having a urotropine concentration of 60g / L;

[0089] b2. The volume ratio of the inorganic catalyst liquid to the organic synthesis liquid is 5:2, and the inorganic catalyst liquid is added to the organic synthesis liquid, and the reaction is carried out at room temperature for 22 hours. The solid phase product is filtered and dried at room temperature for 10 hours to obtain polyaminostyrene.

[0090] Step [3] converting the poly (3-thiopheneamide) on the surface of the copper foam substrate into a poly (3-thiopheneamide) / polyaminostyrene copper coordination polymer, specifically comprising the following operations:

[0091] c1. Methyl isobutylene copper, copper methanesulfonate and β-naphthalenesulfonic acid are added to deionized water and mixed to form a base solution B, wherein the amount of methyl isobutylene copper added to the base solution B is 2 g, the amount of copper methanesulfonate added is 130 mL, and the amount of β-naphthalenesulfonic acid added is 50 g; 3-trithiophenecarboxylic acid hydrazine is added to ethylene glycol dimethyl ether to form an additive solution, wherein the amount of 3-trithiophenecarboxylic acid hydrazine added to the additive solution is 25 g per liter; the additive solution is added to the base solution B in a volume ratio of 3:7 to form a conversion solution;

[0092] c2. Immerse the intermediate A in the conversion solution (the weight of the intermediate A immersed in each liter of the conversion solution is 100 g), and at the same time add a certain amount of polyaminostyrene to the conversion solution (the amount of polyaminostyrene added to each liter of the conversion solution is 80 g), heat to 70°C, react for 12 hours, take out the foam copper sample, and dry it under ventilation at room temperature for 8 hours to obtain foam copper with a surface loaded with poly 3-thiopheneamide / polyaminostyrene copper coordination polymer, i.e., the foam copper-based catalytic material.

[0093] Example 3

[0094] Preferred embodiment 3 of the present invention provides a method for preparing a foam copper-based catalytic material for electrochemical degradation of chloramphenicol wastewater, comprising the following steps:

[0095] Step [1] loading poly (3-thiopheneamide) on the surface of the copper foam substrate comprises the following operations:

[0096] a1. Add 3-terthiophenecarboxylic acid hydrazine and 3-thiopheneacetyl chloride to ethylene glycol dimethyl ether and mix to form a base liquid A, wherein the amount of 3-terthiophenecarboxylic acid hydrazine added to the base liquid A is 110 g, and the amount of 3-thiopheneacetyl chloride added is 80 g; sodium bisulfite and urea are added to deionized water to form a sodium bisulfite concentration of 10 g / L, urea concentration of 60 g / L catalytic regulator;

[0097] a2. A certain amount of catalytic regulating liquid is added to the base liquid A to form a loading liquid (the volume ratio of the catalytic regulating liquid to the base liquid A in the loading liquid is 2:9), and the foam copper sample is immersed in the loading liquid (the weight of the foam copper immersed in each liter of the loading liquid is 170 g), and the reaction is carried out at room temperature for 24 hours to obtain a foam copper with poly (3-thiopheneamide) loaded on the surface, which is recorded as intermediate A.

[0098] Step [2] synthesizing polyaminostyrene, specifically comprising the following operations:

[0099] b1. Adding 2-aminostyrene and N,N-dimethylaniline to dimethyl sulfoxide, mixing to form an organic synthesis liquid, wherein per liter of the organic synthesis liquid 2-aminostyrene is added in an amount of 140mL, N,N-dimethylaniline is added in an amount of 70mL; adding urotropine to deionized water, mixing to form an inorganic catalyst liquid having a urotropine concentration of 40g / L;

[0100] b2. The volume ratio of the inorganic catalyst liquid to the organic synthesis liquid was 7:4, and the inorganic catalyst liquid was added to the organic synthesis liquid, and the reaction was carried out at room temperature for 26 hours. The solid phase product was filtered and dried at room temperature for 12 hours to obtain polyaminostyrene.

[0101] Step [3] converting the poly (3-thiopheneamide) on the surface of the copper foam substrate into a poly (3-thiopheneamide) / polyaminostyrene copper coordination polymer, specifically comprising the following operations:

[0102] c1. Methyl isobutylene copper, copper methanesulfonate and β-naphthalenesulfonic acid are added to deionized water and mixed to form a base solution B, wherein the amount of methyl isobutylene copper added to the base solution B is 8 g, the amount of copper methanesulfonate added is 190 mL, and the amount of β-naphthalenesulfonic acid added is 20 g; 3-trithiophenecarboxylic acid hydrazine is added to ethylene glycol dimethyl ether to form an additive solution, wherein the amount of 3-trithiophenecarboxylic acid hydrazine added to the additive solution is 45 g per liter; the additive solution is added to the base solution B in a volume ratio of 2:9, and the conversion solution is formed;

[0103] c2. The intermediate A is immersed in the conversion solution (the weight of the intermediate A immersed in each liter of the conversion solution is 130 g), and a certain amount of polyaminostyrene is added to the conversion solution (the amount of polyaminostyrene added in each liter of the conversion solution is 140 g), heated to 90°C, reacted for 8 hours, and the foamed copper sample is taken out and dried under ventilation at room temperature for 5 hours to obtain a foamed copper with a surface loaded with a poly (3-thiopheneamide) / polyaminostyrene copper coordination polymer, i.e., the foamed copper-based catalytic material.

[0104] Example 4

[0105] Preferred embodiment 4 of the present invention provides a method for preparing a foam copper-based catalytic material for electrochemical degradation of chloramphenicol wastewater, comprising the following steps:

[0106] Step [1] loading poly (3-thiopheneamide) on the surface of the copper foam substrate comprises the following operations:

[0107] a1. Add 3-terthiophenecarboxylic acid hydrazine and 3-thiopheneacetyl chloride to ethylene glycol dimethyl ether and mix to form a base liquid A, wherein the amount of 3-terthiophenecarboxylic acid hydrazine added to the base liquid A is 95 g, and the amount of 3-thiopheneacetyl chloride added is 60 g; sodium bisulfite and urea are added to deionized water to form a sodium bisulfite concentration of 15 g / L, urea concentration of 45 g / L catalytic regulator;

[0108] a2. A certain amount of catalytic regulating liquid is added to the base liquid A to form a loading liquid (the volume ratio of the catalytic regulating liquid to the base liquid A in the loading liquid is 2:7), and the foam copper sample is immersed in the loading liquid (the weight of the foam copper immersed in each liter of the loading liquid is 150 g), and the reaction is carried out at room temperature for 22 hours to obtain a foam copper with poly (3-thiopheneamide) loaded on the surface, which is recorded as intermediate A.

[0109] Step [2] synthesizing polyaminostyrene, specifically comprising the following operations:

[0110] b1. Adding 2-aminostyrene and N,N-dimethylaniline to dimethyl sulfoxide, mixing to form an organic synthesis liquid, wherein per liter of the organic synthesis liquid 2-aminostyrene is added in an amount of 125mL, N,N-dimethylaniline is added in an amount of 50mL; adding urotropine to deionized water, mixing to form an inorganic catalyst liquid having a urotropine concentration of 50g / L;

[0111] b2. The volume ratio of the inorganic catalyst liquid to the organic synthesis liquid was 5:3, and the inorganic catalyst liquid was added to the organic synthesis liquid, and the reaction was carried out at room temperature for 24 hours. The solid phase product was filtered and dried at room temperature for 11 hours to obtain polyaminostyrene.

[0112] Step [3] converting the poly (3-thiopheneamide) on the surface of the copper foam substrate into a poly (3-thiopheneamide) / polyaminostyrene copper coordination polymer, specifically comprising the following operations:

[0113] c1. Methyl isobutylene copper, copper methanesulfonate and β-naphthalenesulfonic acid are added to deionized water and mixed to form a base solution B, wherein the amount of methyl isobutylene copper added to the base solution B is 5 g, the amount of copper methanesulfonate added is 160 mL, and the amount of β-naphthalenesulfonic acid added is 35 g; 3-trithiophenecarboxylic acid hydrazine is added to ethylene glycol dimethyl ether to form an additive solution, wherein the amount of 3-trithiophenecarboxylic acid hydrazine added to the additive solution is 35 g per liter; the additive solution is added to the base solution B in a ratio of 3:8 by volume to form a conversion solution;

[0114] c2. The intermediate A is immersed in the conversion solution (the weight of the intermediate A immersed in each liter of the conversion solution is 115 g), and a certain amount of polyaminostyrene is added to the conversion solution (the amount of polyaminostyrene added in each liter of the conversion solution is 110 g), heated to 80°C, reacted for 10 hours, and the foamed copper sample is taken out and ventilated and dried at room temperature for 6 hours to obtain a foamed copper with a surface loaded with a poly (3-thiopheneamide) / polyaminostyrene copper coordination polymer, i.e., the foamed copper-based catalytic material.

[0115] The above are only preferred embodiments of the present invention. It should be understood that the description of the above embodiments is only used to help understand the method and core ideas of the present invention, and is not used to limit the scope of protection of the present invention. Any modifications, equivalent substitutions, etc. made within the ideas and principles of the present invention should be included in the scope of protection of the present invention.

Claims

1. A method for preparing a foam copper-based catalytic material for electrochemical degradation of chloramphenicol wastewater, characterized in that: The following steps are included: Step [1]: loading poly (3-thiopheneamide) on the surface of the copper foam substrate; Step [2] synthesizing polyaminostyrene; Step [3] converts the poly (3-thiopheneamide) on the surface of the foam copper substrate into a poly (3-thiopheneamide) / polyaminostyrene copper coordination polymer.

2. The preparation method of a foam copper-based catalytic material for electrochemical degradation of chloramphenicol sewage according to claim 1, characterized in that: The step [1] specifically includes the following operations: a1. Add 3-trithiophenecarboxylic acid hydrazine and 3-thiopheneacetyl chloride to ethylene glycol dimethyl ether and mix to form a base liquid A; add sodium bisulfite and urea to deionized water and mix to form a catalytic regulator; a2. Add a certain amount of catalytic regulating liquid to the base liquid A to form a loading liquid, immerse the foam copper sample in the loading liquid, and react at room temperature for 20-24 hours to obtain a foam copper with poly (3-thiopheneamide) loaded on the surface, which is recorded as intermediate A.

3. The preparation method of a foam copper-based catalytic material for electrochemical degradation of chloramphenicol sewage according to claim 2, characterized in that: In step a1, the amount of 3-terthiophenecarboxylic acid hydrazine added to each liter of the base liquid A is 80-110 g, and the amount of 3-thiopheneacetyl chloride added is 40-80 g; the concentration of sodium bisulfite in the catalytic regulating liquid is 10-20 g / L, and the concentration of urea is 30-60 g / L.

4. The method for preparing a foam copper-based catalytic material for electrochemically degrading chloramphenicol sewage according to claim 2, characterized in that: In step a2, the volume ratio of the catalytic regulating liquid to the base liquid A in the loading liquid is 1-2:5-9; and the weight of the foam copper immersed in each liter of the loading liquid is 130-170 g.

5. The method for preparing a foam copper-based catalytic material for electrochemically degrading chloramphenicol sewage according to claim 1, characterized in that: The step [2] specifically includes the following operations: b1. Adding 2-aminostyrene and N,N-dimethylaniline to dimethyl sulfoxide, mixing to form an organic synthesis liquid; adding urotropine to deionized water, mixing to form an inorganic catalyst liquid; b2. Add a certain amount of inorganic catalyst liquid to the organic synthesis liquid, react at room temperature for 22-26 hours, filter the solid phase product, and dry it under ventilation at room temperature for 10-12 hours to obtain polyaminostyrene.

6. The method for preparing a foam copper-based catalytic material for electrochemically degrading chloramphenicol sewage according to claim 5, characterized in that: In step b1, the amount of 2-aminostyrene added to each liter of the organic synthesis liquid is 110-140 mL, and the amount of N,N-dimethylaniline added is 30-70 mL; the concentration of hexamethylenetetramine in the inorganic catalyst liquid is 40-60 g / L.

7. The method for preparing a foam copper-based catalytic material for electrochemical degradation of chloramphenicol sewage according to claim 5, characterized in that: In step b2, the volume ratio between the inorganic catalyst liquid and the organic synthesis liquid is 5-7:2-4.

8. The method for preparing a foam copper-based catalytic material for electrochemical degradation of chloramphenicol sewage according to claim 1, characterized in that: The step [3] specifically includes the following operations: c1. Add copper methyl isobutylene, copper methanesulfonate and β-naphthalenesulfonic acid to deionized water and mix to form a base solution B; add 3-terthiophenecarboxylic acid hydrazine to ethylene glycol dimethyl ether and mix to form an additive solution; add a certain amount of the additive solution to the base solution B and mix to form a conversion solution; c2. Immerse the intermediate A in the conversion solution, add a certain amount of polyaminostyrene to the conversion solution, heat to 70-90°C, react for 8-12 hours, take out the foam copper sample, and dry it under ventilation at room temperature for 5-8 hours to obtain a foam copper with a surface loaded with poly (3-thiopheneamide) / polyaminostyrene copper coordination polymer, i.e., the foam copper-based catalytic material.

9. The method for preparing a foam copper-based catalytic material for electrochemical degradation of chloramphenicol sewage according to claim 8, characterized in that: In step c1, the amount of methyl isobutylene copper added to each liter of the base liquid B is 2-8 g, the amount of copper methane sulfonate added is 130-190 mL, and the amount of β-naphthalenesulfonic acid added is 20-50 g; the amount of 3-terthiophenecarboxylic acid hydrazine added to each liter of the additive liquid is 25-45 g; the volume ratio between the additive liquid and the base liquid B in the conversion liquid is 2-3:7-9.

10. The method for preparing a foam copper-based catalytic material for electrochemical degradation of chloramphenicol wastewater according to claim 8, characterized in that: In step c2, the weight of the intermediate A immersed in each liter of the conversion liquid is 100-130 g, and the amount of polyaminostyrene added to each liter of the conversion liquid is 80-140 g.

Citation Information

Patent Citations

  • Copper complex having electrocatalytic activity on hydrogen peroxide and preparation method thereof

    CN103467498A

  • Pd / foamy copper electrode and preparation method and application thereof

    CN107557770A

  • Electrochemical device and electronic device

    CN117461182A

  • Copper-penicillamine / imidazole nano-enzyme with laccase-like activity as well as preparation method and application of copper-penicillamine / imidazole nano-enzyme

    CN117696118A

  • Preparation method of foamy copper-based adsorption material for treating mercury ion-containing sewage

    CN119114038A